Mental health needs associated with COVID-19 on the diamond princess cruise ship: A case series recorded by the disaster psychiatric assistance team. (15th October 2022) - Tachikawa, Hirokazu; Kubo, Tatsuhiko; Gomei, Sayaka; Takahashi, Sho; Kawashima, Yuzuru; Manaka, Kazunori; Mori, Akira; Kondo, Hisayoshi; Koido, Yuichi; Ishikawa, Hiromi; Otsuru, Taku; Nogi, Wataru
Abstract: Coronavirus disease 2019 (COVID-19) infection prevention measures have led to a variety of mental health issues. Although several self-care methods have been recommended for those quarantined, evidence regarding how best to support quarantined people experiencing a mental health crisis is limited. In February 2020, the Diamond Princess cruise ship was quarantined in Yokohama port, Japan following a passenger testing positive for COVID-19. We were sent to address the mental health issues as the Disaster Psychiatric Assistance Team (DPAT). In the present study, we examined the acute mental health needs of the passengers and crew collected by the DPAT using the standard Emergency Medical Team daily reporting system. We assessed 206 cases (99 men and 107 women) with generic health issues and 127 cases (39 men and 88 women) with mental health issues. Mental health issues including disaster stress-related symptoms were as frequent as physical health events associated with COVID-19. The most significant mental health issue was anxiety, as an acute psychological reaction to the quarantine situation. Women and crews most frequently needed mental health support. Mental health improved in most clients after brief counseling. Although several passengers experienced suicidal ideation, there were no cases of actual suicide attempts during the quarantine period. This case has been regarded as a well-known public health event at the beginning of the COVID-19 era. In addition to physical health support, disaster mental health support was essential to save lives. Our findings may facilitate responses to future quarantines, accidents, and mental health crises.